2013
DOI: 10.1590/0037-8682-0174-2013
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells in situ in different clinical forms of human cutaneous leishmaniasis

Abstract: Introduction Leishmania braziliensis infection induces a large spectrum of lesions that clinically manifest as nodules or papules that progress to ulcers. Although it is already known that T helper cells predominate in the lesions, cytotoxic T cells have also been reported to be present, and their role in leishmaniasis immunopathogenesis is not well known. This study investigated the amounts of CD8+ and granzyme B+ cells in different clinical forms of human cutaneous leishmaniasis (CL). Methods Forty tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
(22 reference statements)
1
14
0
Order By: Relevance
“…Although there was no association between CD8 + T cells expressing granzyme and the area of inflammation in E-CL, there was a correlation between the frequency of CD8 + T cells expressing granzyme and the intensity of the inflammatory reaction in L-CL 26. Moreover, although CD8 + T cells kill L. braziliensis –infected cells, they have an impairment in parasite killing 4,5,23. The inflammatory reaction in both E-CL and L-CL is composed of CD68 + , CD4 + and CD8 + T cells as well as B cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although there was no association between CD8 + T cells expressing granzyme and the area of inflammation in E-CL, there was a correlation between the frequency of CD8 + T cells expressing granzyme and the intensity of the inflammatory reaction in L-CL 26. Moreover, although CD8 + T cells kill L. braziliensis –infected cells, they have an impairment in parasite killing 4,5,23. The inflammatory reaction in both E-CL and L-CL is composed of CD68 + , CD4 + and CD8 + T cells as well as B cells.…”
Section: Discussionmentioning
confidence: 96%
“…Although the T-cell response is important to prevent parasite dissemination, an exaggerated inflammatory response is associated with pathology 22,23. We have previously shown a direct correlation between the frequency of CD4 + T cells expressing IFN and TNF, and CD4 + T cells expressing lymphocyte activation markers with the lesion size 22,24.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, both groups of patients expressed similar concentrations of CD68 cells in order to kill amastigotes in infected cells. However, such cytotoxicity is directly correlated with expressed granzyme causing ulcer development …”
Section: Discussionmentioning
confidence: 99%
“…However, such cytotoxicity is directly correlated with expressed granzyme causing ulcer development. 20,41,42 The comparison of cytokine expression per group (Figure 4) showed that IL-10 was significantly higher than IL-17 and IFNγ. These data suggest an immunological balance between inflammatory-antiinflammatory agents, and such balance was similar for two groups of patients.…”
Section: Ifn-γ Il-17mentioning
confidence: 99%
“…High lymphocyte proliferation is also characteristic of CL, and we showed that DI4G decreased lymphocyte proliferation predominantly in CD8 + T cells rather than in CD4 + T cells. The role of inflammatory and cytotoxic CD8 + T cells in the pathology of CL has been well documented [ 7 , 30 , 36 , 37 ]. More recently, evidence has been brought that CD8 + T cells play a key role not only in the inflammatory response and ulcer development but also in the appearance of metastatic lesions in CL [ 38 ].…”
Section: Discussionmentioning
confidence: 99%